Electrocardiographic changes in experimentally induced myocardial ischaemia following ligation of left anterior descending coronary artery in calves - GUPTA, O P; SINGH, G R (The Indian Journal of Animal Sciences, 2013)
Assessment of electrocardiographic (ECG) changes before and immediately after induced myocardial ischaemia, and at 15 min, 30 min, i hr, 2 hr, 24 hr, 48 hr and 72 hr thereafter indicated increased heart rate immediately after ligation and remained so up to 24 hr and then returned to normal limits by 72 hr. The duration and amplitude of different waves, and mean electric axis calculated in preligated calves were within the normal limits. Interestingly the QS type of QRS complex was present in normal calves. Shift in QRS and T wave vectors, S-T elevation, inversion ofT wave and various arrhythmias were seen at different intervals after coronary ligation. The myocardial ischaemia was induced by ligation of left anterior descending coronary artery.